Probabilitas Perpindahan Penumpang Transportasi Massal Berbasis Rel (Studi Kasus Kereta Api Argo Parahyangan Terhadap Kereta Cepat Jakarta – Bandung) - Rahmatunnisa, Syifa Nurhaliza; Utami, Adita; Nurhidayat, Asep Yayat (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2021)
The high mobility of the community in the Jakarta - Bandung corridor, caused a surge in passengers of Argo Parahyangan Train. To overcome this, the Government of Indonesia is carrying out a National Strategic Project, by building the Jakarta - Bandung High Speed Rail which takes only 36-44 minutes. When the Jakarta - Bandung bullet train starts operating, there will be passengers transfer from Argo Parahyangan Train to Jakarta - Bandung High Speed Rail. To find out how many passengers will move from Argo Parahyangan Train to Jakarta Bandung High Speed Rail, this research surveyed with revealed preference technique, then the data analyzed with binary logit method. The travel attributes used in this study are the time difference and cost different. The results in this study, as many as 97.67% and 97.97% will move from Argo Parahyangan Train to High Speed Rail if the time difference is faster 150 and 165 minutes with a higher cost of Rp 25,000. By the cost is more expensive which is Rp 200,000, as much as 12.9% of participants select move to the High Speed Rail if the travel time is faster 150 minutes and about 14.59% select move to the High Speed Rail if the travel time is faster 165 minutes.